Zaman dağılımının uyku kalitesi üzerindeki etkisi / The time of distribution on sleep quality - KANSU, Abdullah (My University, 2014)
Aim: We aimed to determine the relation between sleep quality and time distribution in subjects having no pathologic sleep structure. Matherial and Method: Medical and Polisomnographic records of subjects between 20-70 years old whom were performed polysomnography because of symptoms related with sleep disorders at Bezmialem Vakif University from 1.10.2012 to 01.10.2013 were assessed for eligilibity for the study. Inclusion criteria were as following: RDI<5 in polysomnography, no having upper way resistance syndrome, having more than 60% sleep efficiency. We evaluated the clinic, demographic parameters and compared the PSG parameters and time distribution. Results and Conclusion: In this study we took the circadian rythm term in a different view comparing according to the time distribution. Fifty male and 51 female enrolled to the study. Median agees of males and females were 41,5 (33-50) and 43 (35-51) respectively. Median of BMI of males and females were 28(25-30) and (28-37) respectively. Median of waist circumference of males and females were 98 cm (92-105) and 99 cm (93-115) respectively. Median of Epworth Sleepiness Scale of males and females 8 (4-16) and 8 (5-10) respectively. Median duration of sleep of males and females were 06:02 h (05:17-06:34) and 06:05 h r(05:30-06:39) respectively. Sleep parameters can alter in different timeframes. Especially RDI levels were significantly altered in different time frames. RDI level in 3rd phase of sleep (03:00-04:30) was significantly higher than 1st phase (00:00-01:30). Similarly we found significant alteration in sleep efficiency. Among the most important paremeters effecting sleep quality are personal and environmental factors such as sleep hygiene, circadian rhytm. The factors effecting sleep hygiene and changing the circadian rhytm lead to disruption of sleep and consequently lead to sleep disorders. In order to improve the sleep quality its essential to fix the personel and environmental conditions. In diagnosis, follow up and management of patients having sleep disorders the parameters associated with RDI such as high body mass index, neck cirumference, Epworth Sleepiness Scale and the personel and environmental conditions should be taken account together.
The time of distribution on sleep quality
Amaç: Bu çalışma ile patolojik uyku yapılanması olmayan bireylerde uyku kalitesi ile zaman dağılımı arasındaki ilişkiyi araştırmayı amaçladık. Gereç ve Yöntem: Bezmialem Vakıf Üniversitesi Tıp Fakültesi Göğüs Hastalıkları Uyku laboratuvarında 01/01/2012 – 01/10/2013 tarihleri arasında uyku bozukluğuna ait semptomlar ile PSG tetkiki yapılmış RDI < 5 saptanmış ve üst solunum yolu rezistansı sendromu düşünülmeyen, diğer uyku bozuklukları ile ilgili tanı almayan, uyku yeterliliği %60'ın üstünde olan 20–70 yaş arası hastaların dosyaları ve PSG kayıtları taranmıştır. Bu hastaların klinik, demografik verileri incelenmiş ve PSG parametreleri zaman dağılımına göre karşılaştırılmıştır. Bulgular: Bu çalışmada normal uykuyu etkileyen sirkadiyen ritim kavramı, zaman dağılımına göre karşılaştırma yapılarak farklı bir açıdan ele alınmıştır. Çalışmaya alınan olguların 50' si erkek, 51'i kadın idi. Olguların yaşlarının medyan değerleri erkekler için 41,5 (33-50) kadınlar için 43 (35-51) olarak bulunmuştur. Olguların VKİ medyan değerleri erkeklerde 28(25-30) kadınlarda 32(28-37), bel çevresi erkeklerde 98 (92-105) kadınlarda 99 (93-115) saptanmıştır. Epworth uykululuk skalası erkeklerde 8 (4-16) kadınlarda 8 (5-10) saptanmıştır. PSG total uyku süreleri saat-dakika olarak bakıldığında erkeklerde 06:02 (05:17-06:34) kadınlarda 06:05 (05:30-06:39) saptanmıştır. Uyku etkinlikleri değerlendirildiğinde erkeklerde %92 (85-96) kadınlarda %90 (82-95) saptanmıştır. Uyku parametreleri gecenin farklı zaman dilimlerinde değişiklik gösterebilmektedir. Özellikle RDI değerleri uyku boyunca gecenin farklı periyotlarında anlamlı değişim göstermiştir. RDI uykunun 3. kısmında (saat 03:00-04:30) 1. kısmına (saat 00:00-01:30) göre anlamlı (p: 0,047) olarak daha yüksek bulunmuştur. Benzer şekilde uyku etkinliğinde de farklı sonuçlar bulunmuştur. Sonuç: Uykuyu etkileyen en önemli parametreler arasında ışık, uyku hijyeni ve sirkadiyen ritim gibi bireysel ve çevresel etmenler de bulunmaktadır. Sirkadiyen ritmi değiştiren, uyku hijyenini etkileyen faktörler gece uyku boyunca kişiyi rahatsız ederek uykunun bölünmesine, sonuç olarak gündüz uykululuğuna, uyku bozukluğu yakınmalarına sebep olabilir. Uyku kalitesini arttırmak için kişisel ve çevresel faktörleri de düzeltmek gerekmektedir. Uyku bozukluğu bulunan hastaların tanısı, takibi ve tedavisinin planlanmasında PSG verileri dışında yüksek VKİ, boyun çevresi, Epworth uykululuk skalası gibi RDI ile ilişkisi gösterilmiş başka klinik değerlendirme parametreleri ve uyku hijyenini etkileyen kişisel, çevresel faktörler birlikte kullanılmalıdır.
Keywords: Research Subject Categories::MEDICINE; Göğüs Hastalıkları